Varietal screening in chickpea against Gram Pod Borer, Helicoverpa armigera under field conditions - Dindor, M A; Panickar, Bindu (Indian Journal of Plant Protection, 2020)
A field experiment was conducted to screen the 14 chickpea genotypes against gram pod borer by using biochemical parameters at Agronomy Instructional Farm, SDAU, Sardarkrushinagar during Rabi 2017-18 and 2018-19. The analysis of two Rabi season 2017-18 and 2018-19 revealed that the maximum and minimum mean larval population of Helicoverpa armigera was 0.58 and 2.32 1581 GJG 3 and ICCV 13111 variety/ genotype, respectively. Percent pod damage was also significantly lower (11.21%) and higher (30.76%) in ICCV 13111, which were clearly depicted in significantly higher (1588 kg/ha) yield in GJG 3 and lower (845 kg/ha), respectively. None of the varieties/ genotypes were found highly resistant to H. armigera. However, varieties/genotypes viz. GJG 3, Dahod yellow, GG 1, RJG 0904 and JG 16 fell resistant category, whereas varieties/genotypes GAG 1107, GJG 0919, RSG 888 and ICCV 13111 were categorized under susceptible group. The content of different biochemical in chickpea plants viz., phenol, flavanoid and tannin indicated negative correlation with larval population of H. armigera while positive correlation was observed with other biochemical parameters total soluble sugar and protein in chickpea.